Definition of the Emmallodera perlifera Species Group (Coleoptera: Tenebrionidae: Scotobiini) from Argentina with Descriptions of Two New Species - Macagno, Hilda B.; Flores, Gustavo E. (Polish Academy of Sciences, 2022)
The genus Emmallodera Blanchard, 1842 (Tenebrionidae: Scotobiini) is widely distributed in western and southern Argentina and partially in southern Chile, inhabiting the biogeographic provinces Patagonian, Chacoan and Monte. The genus Emmallodera is well characterized within Scotobiini by the presence of a single spine on the profemur of its species, as well as by having pointed terminal antennomeres, and the tarsomeres loosely articulated to each other. Within the genus, E. perlifera Burmeister, 1875 is the largest species and is the only one characterized by the presence of tubercles on elytral intervals. Analysis of the recently collected specimens resulted in discovery of two new species (E. payunia Silvestro and Flores sp. nov. and E. andina Silvestro and Macagno sp. nov.), which share the main diagnostic features of E. perlifera but possess enough differences in elytral configuration and male genitalia to confirm that they are not conspecific. Under a deep morphological revision, it can be concluded that all of the three above-mentioned species constitute a well-characterized species-group inside the genus Emmallodera, while each of these taxa inhabits different biogeographic provinces, i.e.: Emmallodera perlifera (Monte and Chaco), E. payunia Silvestro and Flores sp. nov. (Patagonian) and E. andina Silvestro and Macagno sp. nov. (Puna). This paper includes taxonomic characterization of the group, designation of lectotype for E. perlifera, descriptions of the two new species, habitus photographs, illustrations of genital features and a distribution map.
Keywords: Ciencias naturales::Ciencias biológicas::Conservación de la biodiversidad; Taxonomía de insectos